Vector Appropriate Distraction and Reduction of a Neglected Trimalleolar Fracture-Dislocation Performed with a Temporary Intraoperative External Fixator - Jordan Brand; Jay Moran; Brad Yoo (Case Reports in Orthopedics)
Traumatic fractures of the ankle can occur with concomitant tibiotalar dislocations, necessitating complex treatment. These injuries have higher rates of loose bodies, open injuries, postoperative complications, and worse patient reported outcomes compared to ankle fractures without dislocation. Patients with neglected or delayed presentations are associated with even higher rates of postoperative complications and worse outcomes compared to acute injuries. The chronicity of the injury leads to soft tissue contractures and malunited fractures, obligating a care plan which involves gradual reduction with a multiplanar external fixator with or without internal fixation at a later date. We discuss a 60-year-old homeless man who presented four weeks after an open trimalleolar fracture-dislocation and was definitely treated with an acute one-stage procedure. Anatomic reduction and stable fixation was achieved through a lateral malleolus osteotomy, soft tissue releases, TAL, and a temporary intraoperative external fixator. This technique was advantageous in this instance of anticipated patient noncompliance. We advocate for the judicious use of the described technique in similar challenging situations.